E-Learning Concepts and Literature Review (Penerbit Universiti Teknologi Malaysia, 2008)
e-Learning is becoming increasingly significant in tertiary education. More universities are gradually employing e-Learning into their educational programs. Does e-Learning actually revolutionize the way faculty teaches and students learn? How could government and institutions assist in making e-Learning undertaking a worthwhile effort? This book contains nine chapters on e-Learning issues and implementation in higher education. These issues are considered from a number of different angles, including the readiness of the nation towards e-Learning, the role of university administrations, the motivations of the academics and the attitude and experience of the students. These factors are critical in creating a successful environment for e-Learning. The need for change is pressing: not only for e-learning strategies in Malaysian higher institutions, but more generally for enhancement of teaching and learning in order to encourage the diffusion of good practices.